Rate of bloom of beef longissimus lumborum: effects of muscle temperature, age, and oxygen exposure time - C.M. Trater; Melvin C. Hunt (Kansas Agricultural Experiment Station Research Reports, 2003)
Steaks from 12 loins were used to determine the best time and temperature combinations for blooming (development of a bright-red color) of the longissimus muscle at 2, 14, and 26 days postmortem. The lowest temperature (28°F) provided the fastest rate of bloom when the muscle was 2 days postmortem, and 30 minutes were needed to achieve 75% of final bloom color. For meat 14 days old, greater bloom occurred at 35 and 40°F than at 28°F. For meat 26 days old, rate of bloom was equal at all three temperatures. Thus, packers should bloom carcasses one-half hour at 28°F before presenting carcasses for grading, and retailers will need 30 to 40 minutes after cutting to achieve 75% of final bloom at 35° to 40°F.
Keywords: Cattlemen& #x27; s Day; 2003; Kansas Agricultural Experiment Station contribution; no. 03-272-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 908; Beef; Longissimus lumborum; Muscle temperature; Muscle age; Muscle oxygen exposure time